Teknik Squat dan Stoop Menggunakan Electromyography pada Pekerjaan Manual Materials Handling - I Wayan Surata (Institute of Research and Community Outreach - Petra Christian University, 2013)
Manual materials handling has been identified as the most common cause of work-related musculoskeletal disorders. Among the manual material handling activities, lifting has long been regarded as an activity associated with a high risk of low-back pain. Lifting studies have mainly focused on the squat and stoop lifting techniques as an effort to improve the protection of workers from low back discomfort. However, neither is ideal and the benefits of one technique over another have proved inconclusive. The purpose of this study was to examine and compare the squat and stoop lifting techniques through analysis of muscles activation by using electromyography. Six volunteers participated in the study, and were required to lift a weight with squat and stoop techniques, with two types of loading at 1,7 kg and 6,7 kg. Observations were made on the rectus femoris, biceps femoris, and multifidus muscles. The results of study showed that the squat technique had higher levels of muscle activation compared to stoop technique on rectus femoris muscle. On the contrary, squat technique had lower muscle activation compared to stoop technique on biceps fermoris muscle. Meanwhile, both techniques squat and stoop had the same level of muscle activation on multifidus muscle. Conclusion, squat and stoop lifting techniques had the same opportunities to use.